BETA MYRCENE DAN DL-LIMONENE SEBAGAI KOMPONEN UTAMA EKSTRAK KULIT JERUK SIAM (CITRUS NOBILIS) DARI EKSTRAKSI DENGAN METODE SOKHLETASI - Yuniantari, Ni Luh Putu; Erlin Susilowati; Dini Nastiti Anjarsari (Program Studi Kimia, Fakultas MIPA, Universitas PGRI Banyuwangi, 2025)
Orange is one of the plants that cultivated and considered as horticultural plants. One of the regencies which have a lot of oranges crops is Banyuwangi and orange is one of the Banyuwangi commodities. The kind of orange which cultivated in Banyuwangi is Jeruk Siam (Citrus nobilis). Availability of oranges all of the years and the high of oranges consuming caused a lot of peel. To process orange peel be a product that have economics value that is be essentials oil. The aim of this research is to explore the diversity of volatile compounds of Citrus nobilis peel. The method used in this research is soxhletation which n-hexane as solvent. Extract was analyzed by using GCMS-QP2020 NX Shimadzu. Two of major volatile compound was identified as beta myrcene and dl-limonene which had Rt dan % area are 2.501 minutes, 3.75% and 3.113 minute, 41.08% the data was compared to Wiley 9 LIB. The data fragmentation (m/z) of beta myrcene are 41, 43, 53, 69, 93, 107, 121,136. The data fragmentation (m/z) of dl-limonene are 36, 41, 53, 68,79, 93, 107, 121, dan 136.